Nanofibras biodegradáveis eletrofiadas aplicadas à filtração de ar do SARS-CoV-2 Simulado - Mata, Gustavo Cardoso da (2024)
One of the lasting outcomes of the COVID-19 pandemic was the production and deposition of plastics. These materials, particularly disposable face masks, end up in the environment, releasing microplastics and other pollutants. Although the pandemic has ended, disposable face masks continue to be essential in healthcare services and major cities to mitigate the effects of increasing air pollution. This study aimed to create a viable alternative to disposable face masks made from non-degradable polymers. It utilized polyvinyl alcohol (PVA) and chitosan (CS) as natural and biodegradable polymers to produce air filters using the electrospinning technique. Solution properties, such as rheology and conductivity, were investigated using Design of Experiments (DoE), particularly Response Surface Methodology (RSM), to optimize nanofiber production, dimensions, and air filtration capabilities, achieving filtration efficiencies of up to 99%, superior to N95 face masks. Nanostructures present in our electrospun fiber mat, known as spider-nets, were tailored to further enhance the fiber mat properties. Our tests also examined the mechanical properties of the air filters, adjusting their mechanical strength and hydrophobicity, further improving our fibers to withstand higher air filtration velocities. This study has already achieved its main goals, providing a viable and biodegradable alternative to traditional discardable facemasks, complying with regulations worldwide, and contributing to the current trend among scientists to transition to more ecological materials.